Environmental problems of the oil and gas industry in Kazakhstan - Alimbaev, T.; Yermagambetova, K.; Kabyltayeva, S.; Issayev, A.; Kairat, Zh.; Mazhitova, Zh. (International Scientific Conference on Biotechnology and Food Technology (BFT), 2020)
This article examines the environmental problems of the oil and gas sector in the Republic of Kazakhstan. The authors emphasize that for many decades the oil fields of Kazakhstan have developed mainly a raw material management system with extremely high technogenic loads on the environment. It is noted that for Kazakstani economy, oil and gas production and especially their export play a key role in generating income and growth within the gross product. At the same time, the authors point out that the impact of the oil and gas field on the environment in recent years has been characterized by its intensity, diversity and significant scale. The issue of developing new hydrocarbon raw materials deposits is considered, which is accompanied by geological exploration, drilling and construction works, laying of pipelines and roads. The authors come to the conclusion that a strong anthropogenic impact on all components of the environment causes an active change in the chemical and physicochemical properties of the soil, disrupts the hydrological regime of territories, leads to impoverishment and changes in the species composition, structure and productivity of phytocenoses, a reduction in the spatial distribution and number of animal populations. In conclusion, the authors put forward a number of fundamental tasks for solving environmental problems of the industry.